CODE-MIXING IN WHATSAPP (WA) CHAT GROUP IBAD LOVERS - I WY DIRGEYASA (Universitas Negeri Medan, 2019)
The objectives of this study were to find out 1) the types of code-mixing in WhatsApp (WA) chat group IBAD LOVERS, 2) the way of using code-mixing in WhatsApp (WA) chat group IBAD LOVERS, and 3) the reasons for using code-mixing in WhatsApp (WA) chat group IBAD LOVERS. The data are analysed by descriptive qualitative research. The data of this research were from utterances (chat) of participants. The source of data are taken from screenshot of WhatsApp Chat Group IBAD LOVERS from February 22nd 2020 till August 6th 2020 and the online questionnaire. The results of this research showed that 1) there were five types of code-mixing are used by the participants in WhatsApp (WA) chat group IBAD LOVERS, namely: phrase insertion with total number 46 utterances (46%), word insertion with total number 30 utterances (30%), hybrid insertion with total number 11 utterances (11%), clause insertion with total numbers 10 utterances (10%), and expression insertion with total number 3 utterances (3%). 2) There were five ways to show about the using of code-mixing in WhatsApp (WA) chat group IBAD LOVERS, namely: 52 (52%) for chat, 36 (36%) for comment, 7 (7%) for photo’s caption, 3 (3%) for video’s caption, 2 (2%) for link. 3) There were four reasons about the factors of using code-mixing in WhatsApp (WA) chat group IBAD LOVERS, namely: 12 (60%) for talking a particular topic, 4 (20%) for being emphatic on something, 2 (15.3%) for to make utterance clearer, 1 (5%) for intention of clarifying the speech.